Electronic properties of air-exposed GaN(11-00) and (0001) surfaces after several device processing compatible cleaning steps - Auzelle, Thomas; Kowalsky, Wolfgang (Applied surface science, 2019)
We report on the electronic properties of GaN(11¯00) and (0001) surfaces after three different and subsequent device processing compatible cleaning steps: HCl etching, annealing at 400°C in N2 atmosphere, and O2 plasma exposure. The surface electronic properties are quantified, in the dark and under ultraviolet illumination, using X-ray photoelectron spectroscopy and a Kelvin probe. We find that the cleaning steps largely affect the work function and the band bending of both GaN orientations. These modifications are attributed to the presence of different surface states as well as to the formation of adsorbates building up distinct surface dipoles. Besides these results, we detect that under ultraviolet illumination the work function of the surfaces exposed to HCl decreases by at least 0.2 eV without screening of the band bending. We thus attribute the observed surface photovoltage to a photo-induced modification of the surface dipole. Overall, these results emphasize the strong dependence of the electronic properties of air-exposed GaN surfaces on adsorbates. As a result, we advocate the use of the common cleaning steps analyzed here to re-initialize at will GaN(11¯00) and (0001) surfaces into pre-defined states.